To Be A Diplomat, Why Not? (A Case Study on the Studentsâ Enthusiasm towards Model United Nations: An Innovative Teaching Method in the 21st Century) - Nasution, Sukma Septian; Mayangsari, Damona (Sebelas Maret University, 2016)
Model United Nations (MUN) as a teaching method is being developed to be implemented in many schools in many countries to acquire the demands of living in international community. High schools in Indonesia started practicing it in 2010. As this is quite new, its practicality is still frequently rare and quite complicated to do. Therefore, this study aimed at researching the studentsâ enthusiasm towards model united nations as a path to know whether this kind of teaching method is acceptable for them. The subjects of the research were 40 students of PondokPesantren Modern Darul Mursyid, Tapanuli Selatan, North Sumatera who joined the schoolâs English club. This is a qualitative research designed in a case study employing three instruments in collecting the data; interview, observation, and documentation. The interview showed that the students were enthusiastic to implement MUN, curious to know further, and engaged with all of the activities. The observation showed that the students were active, consistent and discipline in following all the activities. While the documentation showed that their success in implementing this kind of teaching method was equipped by their sufficient background of English language mastery. Accordingly, it can be concluded that the studentsâ enthusiasm towards MUN was sophisticatedly high and their capacity to follow the teaching method was satisfying. These findings imply its possibility to be implemented in the class. The suggestion is addressed for teachers to simplify the procedures to make its practicality more tangible to do.Â